Novel end points for clinical trials in young children with cystic fibrosis. (June 2013) - Simpson, Shannon J; Mott, Lauren S; Esther Jr, Charles R; Stick, Stephen M; Hall, Graham L
Cystic fibrosis (CF) lung disease commences early in the disease progression and is the most common cause of mortality. While new CF disease-modifying agents are currently undergoing clinical trial evaluation, the implementation of such trials in young children is limited by the lack of age-appropriate clinical trial end points. Advances in infant and preschool lung function testing, imaging of the chest and the development of biochemical biomarkers have led to increased possibility of quantifying mild lung disease in young children with CF and objectively monitoring disease progression over the course of an intervention. Despite this, further standardization and development of these techniques is required to provide robust objective measures for clinical trials in this age group.